Educational analysis of loneliness and old age in the survival practices of kazan bourgeois women (late 18th - first half of the 19th centuries) - Tatyana Victorovna Bessonova; Nikolaeva Valentina Alexandrovna (Revista on line de Política e Gestão Educacional)
The article is devoted to educational analysis of the everyday life practices of bourgeois widows – one of the most socially vulnerable categories of the urban population. Using various sources, many of which have been first introduced into scholarly discourse, various ways of surviving widows are shown by way of the example of the petty bourgeoisie of Kazan, a large provincial city of the Russian Empire. The micro historical approach to the study made it possible to identify the educational and literary aspects, social feeling and sentiment of this category of Russian townswomen. In light of this, the key role of family in matters of social care which strengthened the subjection of women in society during the considered period was revealed. On the other hand, the necessity to keep themselves, to manage their estate, encouraged women to intense activity, made them more independent and self-reliant, which had been gradually destroying patriarchal stereotypes in gender relations.